THE INFLUENCE WORD OF MOUTH (WOM) ON REVISIT INTENTION: THE MEDIATING ROLE OF DESTINATION IMAGE (CASE STUDY ON DOMESTIC TOURISTS VISITING MOUNT BROMO) - Ayuningtiyas, Galuh Ajeng; Nimran, Umar; Hamid, Djamhur (Profit: Jurnal Adminsitrasi Bisnis, 2014)
The purpose of this research is to study the influence of Word of Mouth (WOM), on Revisit Intention with the intervening effect of Destination Image. 100 questionnaires were distributed to tourists who come to Mount Bromo through convenience sampling approach. The scales of measurement used in this study is Likert scale. Validity and Reliability of the measurement scale were established with the formula analysis correlation Product Moment Pearson and Cronbach’s Alpha. The technique of data analysis in this study use path analysis. Path analysis is a statistical method used to examine the hypothesized (casual) relationship between two or more variables. The empirical result from the path analysis suggests that Word of Mouth (WOM) has influence on Revisit Intention. Word of Mouth (WOM) consists of Organic Word of Mouth and Amplified Word of Mouth. Organic Word of Mouth has a positive significant influence on Revisit Intention. Amplified Word of Mouth has a negative non significant influence on Revisit Mount Bromo but if through Destination Image, Amplified Word of Mouth has a positive significant influence on Revisit Intention. Keywords: Word of Mouth, Organic Word of Mouth, Amplified Word of Mouth, Destination Image, Revisit Intention.